Quantifying grammatical impairments in primary progressive aphasia: Structured language tests and narrative language production. (22nd January 2021) - Mack, Jennifer E.; Barbieri, Elena; Weintraub, Sandra; Mesulam, M.-Marsel; Thompson, Cynthia K.
Abstract: Purpose: This study examined grammatical production impairments in primary progressive aphasia (PPA), as measured by structured tests and narrative samples. We aimed to quantify the strength of the relationship between grammatical measures across tasks, and identify factors that condition it. Three grammatical domains were investigated: overall sentence production, verb morphology, and verb-argument structure. Methods: 77 participants with PPA (34 PPA-G, 16 PPA-L, 15 PPA-S and 12 other) completed a battery of grammatical tests and a narrative language sample was obtained. Accuracy scores were computed for the language tests and the narrative samples were analyzed for both accuracy of selected narrative variables as well as grammatical diversity across the three grammatical domains. Principal components analysis (PCA) and multiple regression were used to examine cross-task relationships for all measures. Results: As expected on the basis of classification criteria, accuracy scores were lower for the PPA-G group as compared to the PPA-L and PPA-S participants for overall sentence production and verb morphology, but not argument structure. Grammatical accuracy in narratives strongly predicted overall language test performance in PPA-G, whereas grammatical diversity in narratives did so in PPA-L, and no significant correspondence between narrative and language test performance was found for PPA-S. For individuals with severe grammatical impairments only, error distribution for both morphology and argument structure was strongly associated in structured tasks and narratives. Conclusions: Grammatical production in narrative language predicts accuracy elicited with structured language tests in PPA. However, unique narrative production patterns distinguish PPA by subtype: accuracy for PPA-G, and grammatical diversity for PPA-L. The impairment in PPA-G is likely to reflect a core impairment in grammar whereas that of PPA-L may be closely tied to the word retrieval and verbal working memory deficits that characterize this variant. This underscores the theoretical distinction between PPA-L and PPA-G, as well as the importance of including grammatical diversity measures in analyses of language production, especially for patients who do not display frank agrammatism. Further, the results suggest that measures of domain-specific language deficits (i.e., verb morphology vs. argument structure) are robust across tasks only in individuals with severe grammatical impairments. Highlights: Grammatical accuracy in narratives predicted test scores in agrammatic PPA (PPA-G). Grammatical diversity in narratives predicted test scores in logopenic PPA (PPA-L). In severe agrammatism, error distributions matched between tests and narratives. The impairment in PPA-G reflects a core perturbation of grammar. . Mild impairments in PPA-L may be tied to working memory or word retrieval.